Compendium of all philosophies: the Sarvadarśanasaṃgraha translated - Bronkhorst, Johannes (Brill's Indological library, 2025)
"The Sarvadarsanasamgraha presents sixteen philosophical systems known to its 14th century author. The first and so far only English translation of the whole of the Sarvadarsanasamgraha dates from the nineteenth century, when few of the source texts used by its author were accessible. This new translation will rectify numerous current incorrect interpretations and misunderstandings of the text"-- Provided by publisher